Evaluation of user interface designs in official websites "Fine Art Colleges Model" (Al-Academy, 2022)
I found that it does not meet some of the requirements, including browsing and organizing structural elements, which is something in which the researcher found a scope for research, and from here she can formulate the problem of her research with the following question: Is there an actual need to develop user interface designs in the websites of Iraqi colleges of fine arts? The research included four chapters (the first chapter - the research problem - the second chapter (theoretical framework), which included three sections, the first is to identify the user interface, the second topic is the structural elements, and the third topic includes the rules of interface design and the dimensions of interaction), as well as the third chapter includes the analysis of models and the separation The fourth contains the results and conclusions.1. The reliability and ease of searching within destination spaces should be emphasized.2. Providing freedom of opinion in opinion via social media links.3. Freedom to use in terms of language selection and settings control icon.4. Take into account the organization and distribution in the interface spaces and use the space distribution correctly